Maternal Knowledge, Family Support, and Early Complementary Feeding Practice in Working Area Pasar Ikan Public Health Center Bengkul - Violita Siska Mutiara; Ruri Maiseptya Sari; Dwi Pepri Harsasi (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Breastfeeding supplements are recommended at 6 months of age. Under the age of 6 months the baby's digestive system does not have an enzyme to digest the food. As a result of complementary feeding of milk may aggravate the work of the baby's organs, baby's intestine also can not work perfectly so it can cause diarrhea, colic and allergic reactions. This study aimed to study the relationship of mother's knowledge and family support with complementary feeding practice (MP-ASI) in infants 6 months in working area of Pasar Ikan Public Health Center Bengkulu. This study used a type of Correlational Descriptive using Cross Sectional research design. The population in this study was all breastfeeding mothers with babies 6 months of age in working area of Pasar Ikan Public Health Center Bengkulu. Number of samples were 42 mothers. Sampling technique in this research used Accidental Sampling. Data collection in this study used primary data obtained directly from respondents using questionnaires and secondary data. Data analysis was done univariat, bivariate with Chi-Square test. The results of the study were : of 42 mothers, 26 mothers (61.9%) gave early complementary feeding practice, 23 mothers (54.8%) had less knowledge, 27 mothers (64.3%) received poor family support, there was significant association between maternal knowledge and early complementary feeding practice with moderate-relationship category, and there was a significant relationship between family support and early complementary feeding practice with moderate-relationship category. Keywords: complementary feeding practice, family support, knowledge